Kepuasan Pengunjung Sebagai Mediator Pengaruh Daya Tarik Wisata Dan Citra Destinasi Terhadap Minat Berkunjung Kembali Ke Taman Rekreasi Cimalati, Cicurug Sukabumi - Pebriani, Shipa; Harini, Sri; Yulianingsih, Yulianingsih (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose - This study aims to determine and analyze the effect of tourist attraction, destination image, and visitor satisfaction on interest in visiting Cimalati Recreation Park again. Novelty - The novelty of this research lies in the combination of three variables, namely tourist attraction, destination image, and visitor satisfaction. This combination of variables has not been widely used simultaneously in previous studies, thus making a new contribution to the understanding of return visit interest. Methods - This research uses a quantitative approach with primary and secondary data. The analysis techniques used include descriptive verification analysis, path analysis, and coefficient of determination (R²) analysis. The research sample consisted of 100 visitor respondents who had made at least one visit to the Cimalati Recreation Park. Findings - The results showed that tourist attraction and destination image have a direct positive and significant effect on visitor satisfaction, destination image, tourist attraction and visitor satisfaction have a direct positive and significant effect on revisit interest, tourist attraction and destination image have an indirect positive and significant effect on revisit interest through visitor satisfaction.